Evaluation of Socio-Demographic Characteristics in Primary Headache Patients in Tertiary Care Hospital (Journal of Dhaka National Medical College & Hospital, 2020)
Objectives: To find out socio demographic profile of headache patients who presented in neurology outdoor in Dhaka National Medical College & Hospital.Methodology: It was a cross sectional observational study among 100 patients presented in Neurology OPD from the period of January 2018 to June 2018 in Dhaka National Medical College Hospital (DNMCH). A preformed questionnaire was used to collection data and was analyzed with STATA 10 software.Results: Among 100 headache patients most of them were TTH (72%) rest of them were Migraine (28%) and female predominant (76%) age between 34.2+9.8. Most of them are sedentary worker (96%) and from lower middle class family (76%) and according to educational qualification 94% are undergraduate, among them 24% were illiterate and rest of 70% studied up to HSC and only 6% were graduated and above.Conclusion: Sociodemographic profile has an impact on headache character, so we need to recognize these sociodemographic profiles for proper management of headache patients.J. Dhaka National Med. Coll. Hos. 2020; 26 (01): 13-15